Frailty and quality of life of older adults: a study in a rural area - Jesus, Isabela Thaís Machado de; Generoso, Fernanda Karoline; Rossetti, Estefani Serafim; Ottaviani, Ana Carolina; Santos Orlandi, Ariene Angelini dos; Zazzetta, Marisa Silvana (Revista Kairós-Gerontologia, 2019)
To relate the frailty and the life quality of older adults in a rural area. Cross-sectional and descriptive study using a quantitative method. 30 older adults participated in this investigation. As to the relationship of frailty with the life quality, it was obtained moderate correlation magnitude with statistical significance. The findings reinforce the premise that the level of frailty is influenced by multidimensional factors.